INVESTIGATION OF ANTHELMINTIC ACTIVITY OF AN IGNORED PLANT 'KYLLINGA NEMORALIS' TUBER - A POTENTIAL HOPE - PULAK MAJUMDER, (International Journal of Pharma and Bio Sciences, 2013)
Medicinal plants belongs to the oldest known health care products that have been used by mankind all over the world in the form of folklore medicines or traditional medicines or ethno medicines. The use of herbal drugs, extracts and their remedies have significantly increased throughout the world and the ‘green revolution’ in terms of herbal medicines has now achieved astonishing popularity. The present investigation was aimed on the Phytochemical evaluation and screening of root extract of Kyllinga nemoralis for its antihelmintic efficiency in animal model which has traditional claims also. The phytochemical tests revealed the presence of limited phytoconstituents like carbohydrates, alkaloids and volatile oils in ethanolic tuber extract. The anthelmintic activity of ethanolic extract was investigated by employing animal model. The results were compared with standard drugs like Piperazine citrate and Albendazole. In animal model the parameters studied include paralysis time followed by death time. In this animal model, the ethanolic tuber extracts treated animals showed significant dose dependent anthelmintic activity compared to control group and also results were comparable with standards treated animals. The ethanol tuber extracts of K. nemoralis promote remarkable anthelmintic activity and hence can be suggested for treating various types of worm infections in human beings too.